Bridging the Gap: Exploring Borrowers' Perspectives on Peer-to-Peer Lending and Financial Literacy in Small Businesses - Mohammad Chaidir; Grace Yulianti (STIE KASIH BANGSA, 2025)
This qualitative literature review explores the perspectives of borrowers in small businesses regarding peer-to-peer (P2P) lending and financial literacy. It examines the growing importance of P2P lending as an alternative financing option for small businesses, especially in contexts with limited access to traditional financial institutions. The review highlights that while P2P lending offers flexibility and accessibility, borrowers' financial literacy remains a critical factor in ensuring successful engagement with these platforms. Limited financial knowledge can lead to poor decision-making and repayment challenges. This study underscores the need for financial education to bridge the gap, improve borrowers' decision-making processes, and enhance the overall effectiveness of P2P lending in supporting small business growth. The findings contribute to a deeper understanding of how financial literacy impacts borrowers' experiences with alternative financing models.